Lightning Current Distribution of the First and Subsequent Strokes Based on the Lightning Location System: Survey in Yunnan Power Grid - Yutang Ma; Hongchun Shu; Changxin Xiao; Gaohui Yang; Chengwei Xie; Mengmeng Zhu; Pulin Cao (Atmosphere)
Lightning is an electrical discharge phenomenon in the atmosphere caused by charge separation in clouds, which is divided into cloud-to-ground (CG) and cloud-to-cloud (CC) lightning. In recent years, research on the characteristics of multiple-stroke ground lightning and the amplitude of lightning currents has attracted significant attention. The amplitude of lightning currents serves as fundamental data for lightning protection in power systems. Its accurate measurement is crucial for designing and safeguarding power systems. This paper obtains data from a lightning location system and analyzes the probability density distribution of lightning current amplitudes. It is found that the median of lightning currents gradually decreases with an increasing number of multiple strokes, and there is a trend in the change of lightning current steepness. As the number of strokes increases, the median value of amplitude distribution gradually decreases, while the steepness coefficient shows an increasing trend. These research findings contribute to a deeper understanding of the characteristics of lightning and provide important references for lightning prevention and disaster reduction.